Digital Learning Transformation through the I-RME Learning Model Supported by LMS: Improving Students' Independence in Mathematics Learning - Vepi Apiati; Sugiman Sugiman; Sri Andayani; Heri Retnawati; Wahyu Setyaningrum (Jurnal Riset Pendidikan Matematika, 2026)
The advancement of technology in the digital era has shifted mathematics learning from teacher-centered to student-centered approaches, emphasizing the importance of students’ learning independence. Learning Management Systems (LMS) have the potential to support this transformation; however, their use in fostering learning independence remains limited. Therefore, integrating technology with appropriate learning models is essential. This study aims to examine the effectiveness of digital learning transformation through the implementation of an LMS-supported I-RME (Inquiry–Realistic Mathematics Education) learning model in enhancing students’ independence in learning mathematics. A quasi-experimental design was employed involving 198 tenth-grade students from two senior high schools in Tasikmalaya. The experimental group received instruction using the LMS-supported I-RME learning model, while the control group was taught using the I-RME learning model without LMS and conventional methods. Students’ learning independence was measured using a validated and reliable questionnaire. The results indicate that the experimental group demonstrated greater improvement in learning independence compared to the control group. These findings suggest that the LMS-supported I-RME learning model is effective in promoting students’ independence in learning mathematics and provides more optimal outcomes than both non-LMS I-RME learning model and conventional approaches.